2020
DOI: 10.1108/jic-10-2019-0235
|View full text |Cite
|
Sign up to set email alerts
|

Do intellectual capitals matter to firm value enhancement? Evidences from Taiwan

Abstract: PurposeThe purpose of this study is to find evidence of the impact of intellectual capital on firm value, and, in turn, enhance the existing literature which lacks consensus on it. By employing some distinctive proxies for human capital, innovation capital, customer capital and process capital, this study might provide valuable information for firms to make strategic decisions.Design/methodology/approachThis study uses Tobin's Q to represent firm value and various variables to be the proxies for intellectual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 113 publications
7
30
1
4
Order By: Relevance
“…Bayraktaroglu et al [71] declared that INC directly leads to the increase in firms' productivity. As Ni et al [72] revealed, INC might be beneficial for firms to improve firm value because firms need to search for new ideas to achieve innovation. erefore, we propose the following hypothesis.…”
Section: Hypothesis 4 (H4) Rc Can Enhance Firm Performance Inmentioning
confidence: 99%
“…Bayraktaroglu et al [71] declared that INC directly leads to the increase in firms' productivity. As Ni et al [72] revealed, INC might be beneficial for firms to improve firm value because firms need to search for new ideas to achieve innovation. erefore, we propose the following hypothesis.…”
Section: Hypothesis 4 (H4) Rc Can Enhance Firm Performance Inmentioning
confidence: 99%
“…Models (10) and ( 12) reveal that INC and RC have an S-shaped relationship with FC. INC becomes a driver of wealth generation, economic growth, and human well-being (Kirikkaleli & Ozun, 2019;Ni et al, 2021). For automotive companies, digital technologies in vehicles, such as autonomous driving systems, require a huge amount of money, which in turn might lower firms' current profits.…”
Section: Resultsmentioning
confidence: 99%
“…While attainment of superior financial performance is a more short-term goal, firm value on the other hand, focuses more on long term sustainability of the company (Vu & Le, 2021). Firm value, which companies are determined to raise, is seen as the main indicator when it comes to evaluating the performance of a business entity (Ni, Cheng, & Huang, 2020). Christina (2019) holds that investable firms significantly increases their market values as well as tangible investment.…”
Section: Firm Valuementioning
confidence: 99%